Effectiveness of SEMPAS Supplementary Feeding in Improving Weight-for Height Status Among Wasting Children Under Five in East Martapura - Novita Ayu Indraswati; Dian Rizeki Finarti; Kiki Rezki Aulia (Rifa'Institute, 2026)
Introduction: Wasting is an acute form of malnutrition characterized by low weight-for-height due to inadequate energy and protein intake, increasing the risk of impaired growth, morbidity, and mortality among children under five years of age. SEMPAS, a locally developed supplementary food made from fish, chicken, and vegetables, is rich in protein and essential nutrients that may support nutritional recovery. Objective: This study aimed to determine the effect of SEMPAS supplementary recovery feeding on the nutritional status of wasted children under five years of age in the East Martapura Community Health Center catchment area, Indonesia. Method: A pre-experimental study using a one-group pretest–posttest design was conducted among five wasted children selected through purposive sampling. Nutritional status was assessed using the weight-for-height indicator before and after the intervention. Results and Discussion: Before the intervention, all participants (100%) were classified as wasted. After receiving SEMPAS, 60% showed improvement and were no longer classified as wasted, while 40% remained wasted. Conclusion: SEMPAS supplementary feeding demonstrated potential benefits in improving the nutritional status of wasted children and may serve as an alternative locally sourced supplementary food in nutritional rehabilitation programs